Khalwat dan Keamanan Digital Perempuan: Perspektif Hadis terhadap Interaksi Lintas Gender di Era Siber - Alwi Padly Harahap (Arba: Jurnal Studi Keislaman, 2025)
In the digital era, online harassment against women is increasing along with the rapid development of communication technology. One of the contributing factors is uncontrolled online interactions, including private conversations that can open up opportunities for indecent acts. In Islam, the prohibition of khalwat (being alone between a man and a woman who are not mahram without supervision) is relevant in the digital context to prevent gender-based cybercrime. This study aims to analyze the implementation of the prohibition of khalwat in the hadith as a preventive strategy against online harassment against women. The method used is qualitative research with a descriptive-analytical approach to the hadiths that discuss khalwat, as well as a contextual analysis of the phenomenon of digital harassment. The results of the study show that the concept of khalwat can be applied in digital interactions by avoiding private communications that have the potential to cause slander or harassment. This principle is in line with Islamic teachings that emphasize caution in interactions between men and women. In conclusion, the implementation of the prohibition of khalwat in digital communication can be a preventive step in preventing online harassment against women, especially through education on social media ethics and strengthening regulations that support digital security.